KETERKAITAN SEKTOR TANAMAN BAHAN MAKANAN DENGAN SEKTOR PEREKONOMIAN LAINNYA DI PROPINSI SUMATERA UTARA - Hotman, Jan (Jurnal Organisasi dan Manajemen, 2007)
This study aimed to know performance of food crops sector in North Sumatera Province. The sector roles were analyzed by linkages. The data was the North Sumatera Province Input Output data, year 2002 update from year 2000. Data was analyzed by using Grimp 7.1. The result show indicate that linkages the food crops sector haven law with other sectors